Exploring potential drivers of E uropean biomass burning over the H olocene: a data‐model analysis - Chiara Molinari; Veiko Lehsten; Richard H. W. Bradshaw; Mitchell J. Power; Peter Harmand; Almut Arneth; Jed O. Kaplan; Boris Vannière; Martin T. Sykes (Global Ecology and Biogeography, 2013)
Aim To reconstruct spatial and temporal patterns of European fire activity during the Holocene and to explore their potential drivers, by relating biomass burning to simulated biotic and abiotic parameters. Location E urope. Methods Holocene fire activity was investigated based on 156 sedimentary charcoal records from lakes and peat bogs across E urope. Charcoal data covering the last 9000 years were statistically compared with palaeoclimate data derived from the M ax P lanck I nstitute for Meteorology/ U niversity of W isconsin‐Madison E arth S ystem M odel, with vegetation and fire indices simulated with the dynamic vegetation model lpj ‐ guess and with two independent scenarios of past anthropogenic land‐cover change. Results The combined sedimentary charcoal records suggest that there was little fire activity during the early and the middle Holocene compared with recent millennia. A progressive increase in fire frequency began around 3500 cal. yr bp and continues into the late Holocene. Biomass burning rose sharply from 250 cal. yr bp onwards, reaching a maximum during the early Industrial Era and then declining abruptly. When considering the whole Holocene, the long‐term control of fire is best explained by anthropogenic land‐cover change, litter availability and temperature‐related parameters. Main conclusions While the general patterns found across E urope suggest the primary role of vegetation, precipitation and temperature‐related parameters in explaining fire dynamics during the early Holocene, the increase in fire activity observed in the mid–late Holocene is mainly related to anthropogenic land‐cover changes, followed by vegetation and temperature‐related parameters. The 20th‐century decline in biomass burning seems to be due to increased landscape fragmentation and active fire suppression policies. Our hypothesis that human activities played a primary role in Holocene biomass burning across Europe could be tested by improved palaeoclimate reconstructions and more refined representations of anthropogenic fires in climate and vegetation models.